Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Pada Materi Benda-Benda di Sekitar Kita Bagi Siswa Kelas V UPTD SDN 70 Parepare - Israwaty, Ila; Syam, Natriani; Asti, Andi Fajar (Seminar Nasional LP2M UNM, 2023)
Abstract. The aim of this research is to determine the effect of the Problem Based Learning (PBL) model on learning outcomes regarding the objects around us for Class V UPTD SDN 70 Parepare students. The sample in this research was class V students of UPTD SDN 70 Parepare. The use of the Quantum Teaching method is carried out through 5 stages which include (1) Orienting students to the problem, (2) Organizing students to learn, (3) Guiding individual/group investigations, (4) Developing and presenting work results, (5) Analyzing and evaluate the problem solving process. This research procedure was carried out in three stages, namely; (1) Giving Pretest, (2) Giving Treatment, (3) Giving Posttest. It was found from this research through the results of data analysis that the use of the Problem Based Learning Model influences learning outcomes regarding the objects around us for Class V UPTD SDN 70 Parepare students. This is because in the Problem Based Learning (PBL) model, students are actively involved in the teaching and learning process both at the beginning of learning until the end of learning so that it can create an effective and efficient learning environment.  Keywords: learning outcomes, objects around us, Problem Based Learning